The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1136/jcp.35.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Feulgen-hydrolysis profiles in cells exfoliated from the cervix uteri: a potential aid in the diagnosis of malignancy.

Abstract: SUMMARY By varying the time of hydrolysis for the Feulgen reaction, done under conditions that protect the backbone of the DNA, it is possible to distinguish three species of DNA that are characterised by their lability to acid hydrolysis. The most labile DNA was found, in greatest proportions, in malignant cells; this may be helpful in diagnostic cytology. The fact that the cytologically normal cells, in grade V smears, also show this labile DNA may well facilitate cytological screening even in those smears t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 16 publications
(14 reference statements)
3
10
0
Order By: Relevance
“…These would not be contradictory to our results. Our findings are also consistent with the similar, though diminished, lability to Feulgen hydrolysis of cytologically normal cells in smears from cervical cancer patients compared to their counterparts in smears from normal patients [58].…”
Section: Dna Histograms In the Presence Of Heparinsupporting
confidence: 94%
“…These would not be contradictory to our results. Our findings are also consistent with the similar, though diminished, lability to Feulgen hydrolysis of cytologically normal cells in smears from cervical cancer patients compared to their counterparts in smears from normal patients [58].…”
Section: Dna Histograms In the Presence Of Heparinsupporting
confidence: 94%
“…Sandritter showed that CIS of the uterine cervix is an aneuploid lesion and postulated an increasing DNA content as normal squamous epithelium progresses to invasive carcinoma. 18 -23 In 98% of squamous cell carcinomas of the uterine cervix, DNA aneuploidy as the cytometric equivalent of cytogenetic aneuploidy can be detected, 16,24,25 but so far it has not been found in normal or in reactive squamous cells of the cervix. 20,26,27 Precancerous lesions of the uterine cervix show cytogenetic aneuploidy 28 as a marker of transition into aneuploid carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…The increased nuclear expression of GST was consistent, in that the intenincreasedĩn al bu on:aeo;CN oee, enoeria A. incraseds inells but onecasualosbe ofCNtowiever,y endocervical cells visually in a cervical smear preparation, but an automated process would require a second marker. For example, nuclear GST positive cells could be evaluated for DNA content (Millet et al, 1982), or endocervical cells discounted by staining for an antibody specific for simple epithelium. The expression of GST by immature squamous metaplasia is particularly disappointing as this lesion may be mistaken for CIN on both cytology and histology.…”
Section: Discussionmentioning
confidence: 99%